Development forestry industry and implementation of «green» tourism in Ukraine on base of ecological marketing - Добрянська, Вікторія Вікторівна; Глущенко, Тетяна Станіславівна (Technology audit and production reserves, 2015)
The article is devoted to the idea of transforming of forestry companies from ones carrying function of the forest keeping into ones with commercial activity according to market requirements. This transition can be accomplished through the use of marketing approach. The implementations of the concept of marketing allow solving both the problem of financing of forest enterprises in Ukraine and meet the needs of the market by environmentally friendly goods and services. Marketing studies have proven both the ability to create the production and sales of wood products and the provision of services of "green tourism". The transition to such a method of forestry management can be carried out without external funding. Environmental Marketing will provide not only the organization of the new production and sales of products and services of green tourism, but also the multiplying the forest resources. Studies have shown the possibility of successful and profitable business for enterprises and companies engaged in forestry in accordance with all environmental requirements.